Tracking consensus for uncertain nonlinear multi-agent systems under cloud-based event-triggered coordination - Hong, Shanshan (2023)
This paper considers the cloud-based event-triggered coordination problem of uncertain high-order nonlinear multi-agent systems. The communication among agents is realized by indirect and asynchronous access to a shared cloud database. A self-triggered extended state observer (ESO) is first designed to estimate the total uncertainty. Based on the output of the ESO, an event-triggered controller is proposed. It is proved that under the proposed output feedback controller, the multi-agent system can track a virtual leader. We also show that Zeno behavior from output sampling or controller update will never happen. Finally, a numerical example and a vehicle platoon example are provided to corroborate the obtained theoretical results.